Criminal Justice System Based on The Concept Ofrestorative Justice - Try Sarmedi Saragih (LEGAL BRIEF, 2021)
In a country, of course, there are several concepts of legal justice that are adopted and applied to solve a crime and criminalization that occurs in the wider community, as well as in the settlement process which always uses several different concepts, there are those who solve it through a system. state law and there are those who resolve it with a judicial process on the basis of mutual deliberation. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the legal system of restorative justice is a judicial concept in which the settlement process focuses on the peace and kinship system, this concept is certainly very different from the concept of justice adopted by the nation. In Indonesia, where the concept of criminal and civil law is a judicial process that is still adhered to by our current government, implementing a restorative justice justice system in Indonesia will clearly create a new dynamic from a legal perspective as well as from a public perspective, because the principles of justice are both has a very basic difference with the different settlement processes.